Streamlining the analysis of phishing emails using Artificial Intelligence - Fernandes, Eduardo Rocha (2024)
The increasing sophistication and frequency of email phishing attacks pose a significant challenge to cybersecurity. This thesis explores the integration of Artificial Intelligence (AI), specifically Natural Language Processing (NLP) and Machine Learning (ML)/Deep Learning (DL) techniques, to enhance the detection of phishing emails and emotion analysis. By using AI-driven NLP modules, this study aims to develop an AI-based solution that accurately detects phishing emails and includes automated response capabilities. Tested in a local environment, the proposed framework demonstrates its potential to improve phishing detection efficiently. Ultimately, this research contributes to the cybersecurity field by providing a comprehensive, AIpowered framework for more robust phishing email detection.